Instagram as a Social Service Information Media: Analysis of Islamic Digital Communication in the Public Relations of the Medan City Social Service Ministry - Aulia, Tadzkiya; Ritonga, Elfi Yanti (UIN Sunan Ampel Surabaya, 2026)
The use of social media has transformed public communication by enabling government institutions to disseminate information more quickly, visually, and interactively. This study examines the use of Instagram @bahagia_medan as a social service information medium and analyzes the implementation of Islamic digital communication principles by the Public Relations unit of the Ministry of Social Affairs in Medan. This study employed a qualitative descriptive-interpretive approach. Data were collected through observation of 30 Instagram posts published between September 25, 2025, and March 15, 2026, in-depth interviews with public relations officers, Instagram administrators, and content management staff, as well as documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing. The findings show that Instagram is managed collaboratively and functions as a gateway communication medium for disseminating information on social programs, social assistance, and services for vulnerable groups. Content is predominantly presented as activity documentation and informational posts, while practical information on service procedures, requirements, complaints mechanisms, and access pathways remains limited. The management of content reflects the values of tabayyun, shiddiq, amanah, qaulan sadidan, and qaulan layyinan through verification, factual messages, accountability, and polite language. However, low audience engagement, limited interactive content, human resource constraints, algorithmic changes, and unequal digital access remain major challenges. The study concludes that Instagram should be strengthened as an inclusive, responsive, and ethically grounded supporting medium for social services through more accessible, interactive, and audience-oriented content.